NMDARs mediate peripheral and central sensitization contributing to chronic orofacial pain - Liu, Ya-Jing; Li, Yue-Ling; Fang, Zhong-Han; Liao, Hong-Lin; Zhang, Yan-Yan; Lin, Jiu; Liu, Fei; Shen, Jie-Fei (Frontiers in Cellular Neuroscience, 2022)
Peripheral and central sensitizations of the trigeminal nervous system are the main mechanisms to promote the development and maintenance of chronic orofacial pain characterized by allodynia, hyperalgesia, and ectopic pain after trigeminal nerve injury or inflammation. Although the pathomechanisms of chronic orofacial pain are complex and not well known, sufficient clinical and preclinical evidence supports the contribution of the N-methyl-D-aspartate receptors (NMDARs, a subclass of ionotropic glutamate receptors) to the trigeminal nociceptive signal processing pathway under various pathological conditions. NMDARs not only have been implicated as a potential mediator of pain-related neuroplasticity in the peripheral nervous system (PNS) but also mediate excitatory synaptic transmission and synaptic plasticity in the central nervous system (CNS). In this review, we focus on the pivotal roles and mechanisms of NMDARs in the trigeminal nervous system under orofacial neuropathic and inflammatory pain. In particular, we summarize the types, components, and distribution of NMDARs in the trigeminal nervous system. Besides, we discuss the regulatory roles of neuron-nonneuronal cell/neuron-neuron communication mediated by NMDARs in the peripheral mechanisms of chronic orofacial pain following neuropathic injury and inflammation. Furthermore, we review the functional roles and mechanisms of NMDARs in the ascending and descending circuits under orofacial neuropathic and inflammatory pain conditions, which contribute to the central sensitization. These findings are not only relevant to understanding the underlying mechanisms, but also shed new light on the targeted therapy of chronic orofacial pain.